Chemistry and Biochemistry of Winemaking, Wine Stabilization and Aging - Fernanda Cosme; Fernando M. Nunes; Luís Filipe-Ribeiro (IntechOpen, 2021)
This book, written by experts, aims to provide a detailed overview of recent advances in oenology. Book chapters include the latest progress in the chemistry and biochemistry of winemaking, stabilisation, and ageing, covering the impact of phenolic compounds and their transformation products on wine sensory characteristics, emerging non-thermal technologies, fermentation with non-Saccharomyces yeasts, pathways involved in aroma compound synthesis, the effect of wood chips use on wine quality, the chemical changes occurring during Port wine ageing, sensory mechanisms of astringency, physicochemical wine instabilities and defects, and the role of cork stoppers in wine bottle ageing. It is highly recommended to academic researchers, practitioners in wine industries, as well as graduate and PhD students in oenology and food science.